Kultura organizacyjna jako czynnik warunkujący innowacyjność przedsiębiorstw przemysłu spożywczego - Strychalska-Rudzewicz, Anna (Organizational Culture as a Factor Influencing Innovation in Food Industry Enterprise, 2006)
Based on literature study the author proves that organizational culture is one of main determinants of innovation in a company. Factors stimulating the creation of innovation are among the following: shared vision and mission, which are focused on innovation, cooperative work, flexibility of a company, creative people, time for innovation, management support, reward and recognition for innovation, mistake handling in innovative process, open communication. On the basis of the analysis of organizational culture in chosen food industry enterprises the author appoints these elements of culture which should be changed in order to improve innovation of the companies.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 2, s. 357-364